Correlations Between Preseason Functional Test Scores and Game Performance in Female Collegiate Volleyball Players - Jason Brumitt; Christopher Patterson; Robert Dudley; Eric Sorenson; Tyler Cuddeford; Heidi Cooke; Linda Froemming (North American Sports Medicine Institute, 2022)
# Background Functional tests (FT) are assessment tools that attempt to evaluate balance, flexibility, strength, power, speed, or agility through performance of gross motor skills. FT are frequently administered by coaches or sports medicine professionals to evaluate athletic ability, to predict performance, to identify athletes at risk for injury, or to evaluate an athlete's ability to return to sport after injury. Functional tests which can provide accurate or predictive information regarding athletic ability would be advantageous to coaching staffs or medical professionals. # Purpose The primary purpose of this study was to identify correlations between preseason FT scores and in-season game statistics in a cohort of female collegiate level volleyball (VB) players. A secondary purpose was to present FT descriptive data for this cohort based on level of competition, player position, and starter status. # Study Design prospective cohort; correlational # Methods One hundred and thirty-one female collegiate VB players representing three levels of competition completed four FT \[standing long jump (SLJ), single-leg hop (SLH), lower extremity functional test (LEFT), and the Y-Balance Test - Lower Quarter (YBT-LQ)\] at the start of the preseason. Player statistics were collected from team records at the completion of the season. # Results Starters performed significantly better on all tests. There were moderate negative correlations between LEFT scores and game statistics for liberos, defensive specialists, and outside hitters. There were moderate positive correlations between YBT-LQ composite scores and game statistics for liberos, defensive specialists, hitters, and middle blockers. There were also low to moderate level positive correlations between SLJ and SLH scores and game performance for outside hitters. There were low to moderate level positive correlations between SLH scores and game performance for middle blockers and opposite side hitters. # Conclusions The results of this study indicate that there are low to moderate correlations between some preseason functional test scores and some game statistics. The SLJ, SLH, LEFT, and YBT-LQ tests may help coaches with talent identification and/or may influence training strategies. # Level of Evidence 3